Pigments from the Zuiddorp (Zuytdorp) ship sculpture: Red, white and blue? - Van Duivenvoorde, W.; Kaiser, B.; Megens, L.; Van Bronswijk, Wilhelm (2015)
The Dutch East India Company ship Zuiddorp (also known as Zuytdorp) met its demise in 1712 at the base of steep cliffs along the Western Australian coast. Material from the shipwreck includes an extraordinary example of a caryatid herm from the ship's stern counter. A recent study of this sculpture and the pigments found on its surface demonstrates Zuiddorp's archaic stern construction and adornment, which is more of a late 17th-century, than an early 18th-century, Dutch Indiaman. This paper discusses the results of this study and emphasizes how the smallest pieces of evidence can broaden our understanding of contemporaneous regional Dutch East India Company shipbuilding practices. © Society for Post-Medieval Archaeology 2016.